Extracts of leaves and flowers as corrosion inhibitors of vegetable origin (Research, Society and Development, 2019)
Aqueous and ethanolic extracts of leaves and flowers of Unxia kubitzkii H. Rob were evaluated as corrosion inhibitors of plant origin for P110 carbon steel in the presence of HCl 1.0 mol.L-1. The inhibition efficiencies of the extracts were calculated from the corrosion rates obtained by gravimetric assays with variation in the extracts concentration. The lowest corrosion rates were identified with the use of 15% of the extracts, with the aqueous ones coming from the leaves and flowers presenting efficiency values of, respectively, 91.20 and 92.55%. At the same concentration, the ethanolic extract of the leaves provided inhibition efficiency of 93.67%, while the extract of the flowers presented efficiency of 72.13%. Due to inhibition efficiency values above 90% the aqueous extracts of leaves and flowers, as well as the ethanolic extract of the leaves of Unxia kubitzkii H. Rob, present as potential corrosion inhibitors for carbon steel in acid.